COVID-19 and Portuguese Adults with Intellectual Disabilities - Albuquerque, Cristina P. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The COVID-19 pandemic has changed the lives of people all over the world, including in Portugal. This study explores the impact of the pandemic on several life domains of Portuguese adults with Intellectual Disabilities (ID) and their families; identifies the difficulty level in the implementation of the most common preventive measures by adults with ID; addresses the consequences of health authorities’ guidelines in the activities carried out in daycare centers for people with disabilities. A total of thirty-three daycare centers participated; they were attended by a total of 1192 adults at the time the study took place (between the 15th of September 2020 and the 15th of October 2020), and a professional belonging to the daycare center answered an online survey. The results showed that: 1) participants agreed that the pandemic had a negative impact on adults with ID and their families, although only in a percentage of them; 2) in the cases of the adults and families where that negative impact occurred, it was generalized, expressing itself in various life domains; 3) almost all of the preventive measures where considered difficult to apply by adults with ID; 4) the participants agreed that the health authorities’ guidelines influenced the activities that were performed in the daycare centers, i.e., there were less activities, and the existing ones were less diversified, more sedentary and occurring indoors more often. The implications of the negative impact of the pandemic on adults with ID, their families, and the services provided have to be addressed.